Effect of sphincter of Oddi dysfunction on the abundance of biliary microbiota (biliary microecology) in patients with common bile duct stones - Liu, Linxun; Zhao, Zhanxue; Hou, Xiaofan; Wu, Jindu (Frontiers in Cellular and Infection Microbiology, 2022)
Abstract Objective: Biliary calculi, a common benign disease of the gastrointestinal tract, are affected by multiple factors, including diet, lifestyle, living environment, and personal and genetic background. Its occurrence is believed to be related to a change in biliary microbiota. Approximately 10%–20% of symptomatic patients with cholecystolithiasis have choledocholithiasis, resulting in infection, abdominal pain, jaundice, and biliary pancreatitis. This study aimed to determine whether a dysfunction in the sphincter of Oddi, which controls the outflow of bile and separates the bile duct from the intestine, leads to a change in biliary microbiota and the occurrence of biliary calculi. Methods: Forty patients with cholecystolithiasis and choledocholithiasis were prospectively recruited. Bile specimens were obtained, and biliary pressure was measured during and after surgery. The collected specimens were analyzed with 16S rRNA gene to characterize the biliary microbiota. The risk factors of common bile duct calculi were analyzed numerically combined with the pressure in the sphincter of Oddi. Results: Different biliary microbiota were found in all cases. Patients with sphincter of Oddi dysfunction had significantly increased biliary microbiota as well as significantly higher level of systemic inflammation than patients with normal sphincter of Oddi. Conclusions: The systemic inflammatory response of patients with sphincter of Oddi dysfunction is more severe, and their microbial community significantly differs from that of patients with normal sphincter of Oddi, which makes biliary tract infection more likely; furthermore, the biliary tract of patients with sphincter of Oddi dysfunction has more gallstone-related bacterial communities.